Science Education Data Analysis to Improve Student Achievement: An In-Depth Bibliometric Analysis - Habibi, Ahmadi Martha; Al Mubarok, Fahmi Ulum; Chusniatun, Chusniatun; Shobahiya, Mahasri; Musyaffa, Zaim Hilmi (Universitas Muhammadiyah Surakarta, 2024)
This study was conducted to map and analyze the development of research on Science Education Data in publications that have been indexed in Scopus. The method applied is bibliometric analysis, which explores information from publications related to